INFLUENCE OF MODIFIERS ON THE PHYSICAL AND MECHANICAL PROPERTIES OF COMPOSITE MATERIALS BASED ON POLYAMIDE-6 (Academicia Globe: Inderscience Research, 2022)
The article shows the improvement of the physical and mechanical properties of composite materials based on polyamides as a result of the addition of dispersed fillers.